Photosensitivity of Some New Hemicyanines - Dhingra, Vinod; Shrivastava, A.K. (Asian Journal of Chemistry, 2010)
Synthesis and photosensitizing activity of some 4-N, N-bis-2'-carboxyethyl-aminostyryl alkyl ammonium iodides is reported.